Turning Away from Peace? A Media- and Politolinguistic Investigation of Facebook Entries of the Organization Pegida - Greule, Albrecht; Reimann, Sandra; Enzinger, Julia (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
This article aims to show what characterizes Pegida’s language usage (within Facebook entries) and how language is used to achieve approval on or over the social network. It will investigate the extent to which the association uses language as an instrument to recruit supporters and whether Pegida actually uses language as a means of criticizing grievances and opponents. For this purpose, a pragmatic-orientated analysis of Pegida’s Facebook entries will be carried out, in which the linguistic implementation of the text action patterns ADVERTISING and CRITICIZING as well as their relationship to each other will be determined. The theoretical background is formed by findings and methods from both advertising research and political linguistics, which are explained in a first step together with the pragmatic perspective.